Nanotitania-Activated Carbon with Enhanced Photocatalytic Activity: A Comparison Between Suspended and Immobilized Catalyst for Turquoise Blue Removal - Gallo, Jurex; Borja, Josephine; Gallardo, Susan; Ngaotrakanwiwat, Pailin; Salim, Cris; Hinode, Hirofumi (ASEAN Journal of Chemical Engineering, 2011)
The present study aims to synthesize nanoTiO2-AC and evaluate its property and photocatalytic activity using 254nm UV lamp in suspended system and as immobilized catalyst for the color removal of Turquoise blue dye solution. NanoTiO2-AC is synthesized via the sol-gel method and calcined at 400°C. Various ratio (1:10, 2:10 and 3:10) of weight AC / volume of TiO2 sol were investigated. NanoTiO2-AC is immobilized in glass plates using Polyethylene glycol (PEG) as binder. Powder and immobilized catalysts were characterized using BET, SEM-EDX, TGA, FTIR and XRD techniques. The effect of initial dye concentration, initial solution pH, catalyst loading and AC loading were investigated. SEM images confirmed the uniform distribution of nanoTiO2 attached on the surface of AC. Immobilized 1:10 AC/nanoTiO2 has lower surface area compared to powder 1:10 AC/nanoTiO2. Increasing the AC loading in AC/nanoTiO2 increases the dye adsorption in the composite catalyst to as much as 9%. The initial rate of color removal is faster in suspended catalyst compared to immobilized catalyst. In general, suspended catalyst is more efficient than immobilized catalyst. Further, PEG as a binder can be used to immobilize AC/TiO2 in glass with considerable stability.